A systematic review of life cycle sustainability assessment: current state, methodological challenges, and implementation issues - Costa, D. (2019)
The life cycle sustainability assessment (LCSA) is a tool to assess sustainability from a life cycle perspective, which has been receiving increased attention over the years. This work presents a systematic review of the current application of LCSA, presenting the foundations, main methods, current operationalization state, and major challenges to its broad implementation. The review protocol considered the search of keywords in Scopus and Web of Science databases. The search has considered the literature published or in the press until December 2018, resulting in the selection of 144 articles written in English. Of those, 71 articles operationalize LCSA in real case studies, while the remaining consist of review, viewpoint, and methodological development articles. This review demonstrates that the use of LCSA has been increasing in recent years. Today, the most applied approach is to consider LCSA as the sum of life cycle assessment, life cycle costing, and social life cycle assessment because it is built on the methodologies that already exist and are under continuous development. However, the lack of harmonization of the methodology is a central challenge to its operationalization. Therefore, LCSA still requires further improvement in, among others, definition of coherent system boundaries, the development of robust databases to allow the assessment of economic and social perspectives, definition of impact categories that allow comparability between studies, development of impact assessment methods, development of methods to carry out uncertainty analysis, and communication strategies. Besides, further case studies should be developed to support the improvement of the methodology and a better understanding of the interaction of the environmental, economic, and social aspects.